Contribution of some divalent oxides replacing Li2O to crystallization characteristics and properties of magnetic glass–ceramics based on Li2O–Fe2O3–Al2O3–SiO2. Issue 7 (15th May 2016) - Salman, S.M.; Salama, S.N.; Abo-Mosallam, H.A.
Abstract: Magnetic glass–ceramics based on the Li2 O–Fe2 O3 –Al2 O3 –SiO2 glass system, were prepared through controlled heat treatment regimes. The effect of MO/Li2 O replacements (MO=MgO, MnO, ZnO, CdO) on the crystallization process, physical and magnetic properties of the glasses and glass–ceramics were investigated. The crystalline phases formed in the glass–ceramic were lithium metasilicate (Li2 SiO3 ), β-quartz solid solution (ss) (LiAlSi2 O6 ), lithium ferrite (LiFe5 O8 ), Magnesioferrite (MgFe2 O4 ), Jacobsite (MnFe2 O4 ), Franklinite (ZnFe2 O4 ), lithium zinc orthosilicate (γ-Li2 ZnSiO4) and lithium ferrite solid solution Li(Fe, Cd)5 O8 . The density of the prepared glass samples ranged from 2.69 to 2.88 g/cm 3, whereas the corresponding crystalline materials had a density between 2.77 to 2.95 g/cm 3 . The microhardness of the glass samples ranged from 4665 MPa to 5586 MPa and increased to a range of 6268–7042 MPa after crystallization. The saturation magnetization (Ms), remanence magnetization (Mr), and coercivity (Hc) of the glass–ceramics varied from 0.83 to 8.24 emu/g, 0.11 to 0.97 emu/g and 112 to 211 G, respectively. The formation of different MFe2 O4 spinel ferrite magnetic phases instead of LiFe5 O8 led to a greatly enhanced saturation magnetization of the glass–ceramics. Possible use of the prepared glass–ceramics may be realized in microwave and magnetic recording applications as well as in tumors therapy.